Legal Protection and Liability for Multimodal Transport Operators in The Transport of Dangerous and Toxic Goods - Hilda Yunita; Kresna Aron; Joao Nuno Domingues Ferreira (Universitas Negeri Semarang, 2023)
Legal protection protects human rights that harm other people, and every human being is provided with this protection in order they can savor all of their legal right. In other words, legal protection is various legal remedies that must be provided by law enforcement officials to provide a sense of security, both physically and mentally as well as interference from various threats originating from any party. In contrast, transportation law can be interpreted as the overall legal norms and principles governing relationships and consequences of transportation law. This research shows that a form of legal protection for transportation service users can be provided in the form of preventive and repressive legal protection. The responsibility given to service users is in the form of compensation or compensation in the event of damage or loss of goods in the transportation process. There are two approaches used by researchers in this thesis, namely the Legislative Approach and the Conceptual Approach. In this legislative approach, the approach in legal research that provides an analytical point of view of problem-solving legal research is seen from the aspects of the legal concepts that lie behind it or even can be seen from the values contained in the normalization of regulation with the concepts used. Most of these approaches are used to understand the concepts related to normalization in legislation, whether they are in accordance with the spirit contained in the underlying legal concepts.